2016
DOI: 10.1155/2016/6971591
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Detachment in Down Syndrome: Characteristics and Surgical Outcomes

Abstract: Purpose. To determine the functional and anatomic outcomes of rhegmatogenous retinal detachment (RRD) surgery in patients with Down syndrome. Methods. A retrospective chart review was performed of patients with Down syndrome who had undergone surgery for RRD at King Khalid Eye Specialist Hospital between 1995 and 2014. Results. A total of 245 patients with Down syndrome were evaluated during the study period. Eighteen eyes of 15 patients (6.1%) with RRD were identified. Three out of 15 patients (20%) presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Oono et al 19 also suggested that higher intraocular cellular activity and difficulty in maintaining postoperative rest and prone positioning are risk factors for recurrent RD in children with intellectual disability. AlAhmadi et al 20 suggested that the poor prognosis of RD in patients with Down syndrome may be related to the difficulty in compliance with postoperative instructions. In an international multicenter study, Rossin et al 21 reported that the surgical success rates for RD associated with self-injury were the lowest in the recent RD literature.…”
Section: Discussionmentioning
confidence: 99%
“…Oono et al 19 also suggested that higher intraocular cellular activity and difficulty in maintaining postoperative rest and prone positioning are risk factors for recurrent RD in children with intellectual disability. AlAhmadi et al 20 suggested that the poor prognosis of RD in patients with Down syndrome may be related to the difficulty in compliance with postoperative instructions. In an international multicenter study, Rossin et al 21 reported that the surgical success rates for RD associated with self-injury were the lowest in the recent RD literature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have pointed out that RD related to DS is sometimes bilateral, [8] so it is possible that the cases in those studies already had an existing vulnerability apart from a traumatic factor that likely led to RD. In this present case, retinal degeneration spreading in a circumferential direction was observed in a symmetrical position of both eyes, and retinal breaks were observed in and around these degenerations.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, the characteristics of DS-related RD include that it is bilateral, that it is deeply related to trauma resulting from self-injurious behavior, and that detection is delayed due to mental retardation, thus tending to increase the severity of the RD. [8] In regard to the characteristics of causal retinal breaks, numerous studies have reported cases of retinal dialysis due to trauma, [9] yet there have been a few reports of retinal breaks due to causes unrelated to trauma. [4]…”
Section: Introductionmentioning
confidence: 99%
“… 31 One study of 245 patients with Down syndrome found 15 patients (6.1%) had rhegmatogenous RD; of these, a few patients (20% of all patients) had bilateral RDs. 7 It has been reported that more than half of all traumatic RDs were presented late due to late development and chronicity. 7 Poorer outcomes in some patients may be related to late detection because of the patient’s developmental capacity, learning disabilities, and cooperation during the examination, thus exacerbating the poor outcomes associated with RD.…”
Section: Retinal Detachment (Rd)mentioning
confidence: 99%
“… 1 – 6 Physicians are generally most familiar with the facial appearance and intellectual disability associated with Down syndrome. However, Down syndrome has also been associated with numerous ophthalmologic manifestations, 7 12 including patterns of strabismus, 13 , 14 amblyopia, 15 , 16 nystagmus, 17 , 18 nasolacrimal duct obstruction (NLDO), 19 , 20 keratoconus, 21 , 22 eyelid abnormalities, 8 , 23 , 24 cataract, 25 , 26 optic nerve abnormalities, 27 glaucoma, 28 30 and retinal abnormalities. 7 , 31 Whenever appropriate, epidemiology, presentation, mechanisms, and management of these manifestations will be discussed.…”
Section: Introductionmentioning
confidence: 99%